NHDL, a recombinant VL/VH hybrid antibody control for IgG2/4 antibodies - Corinna Lau; Martin Berner McAdam; Grethe Bergseth; Algirdas Grevys; Jack Ansgar Bruun; Judith Krey Ludviksen; Hilde Fure; Terje Espevik; Anders Moen; Jan Terje Andersen; Tom Eirik Mollnes (Taylor & Francis Group, 2020)
The mechanism of action of recombinant IgG2/4 antibodies involves blocking of their target without the induction of effector functions. Examples are eculizumab (Soliris®), which is used clinically to block complement factor C5, as well as anti-human CD14 (r18D11) and anti-porcine CD14 (rMIL2) produced in our laboratory. So far, no proper IgG2/4 control antibody has been available for controlled validation of IgG2/4 antibody functions. Here, we describe the design of a recombinant control antibody (NHDL), which was generated by combining the variable light (VL) and heavy (VH) chains from two unrelated specificities. NHDL was readily expressed and purified as a stable IgG2/4 antibody, and showed no detectable specificity toward any putative antigen present in human or porcine blood. The approach of artificial VL/VH combination may be adopted for the design of other recombinant control antibodies.